Motivating conservation action in the Upper Midwest: Source attention, information seeking and sharing, and farmers' land management decisions - Dara M. Wald; Miguel Diaz‐Manrique; Laura Witzling; Jaqueline Comito (Conservation Science and Practice)
Abstract Adoption of on‐farm conservation strategies, such as edge‐of‐field practices, has the potential to reduce nutrient runoff, promote greater biodiversity, and improve water quality. To date, adoption rates among farmers are extremely low. Communication with farmers has been identified as a vital strategy to encourage the voluntary adoption of these practices and policies that promote on‐farm conservation. Yet little is known about which information sources shape farmers' concerns about conservation practices, perceptions of the risks and benefits of conservation practices, and ultimately, adoption behaviors. Using the Social Amplification of Risk Framework, the Risk Information Seeking and Processing Model, and a cross‐sectional survey, we examined farmers' concerns about nitrate loss and water quality, perceptions of the risks and benefits of conservation practices, attention to messages and information sources, and communication behaviors. We received N = 474 completed surveys. Attention to agricultural associations was associated with decreased concern about nitrates and diminished perceptions of the benefits of edge‐of‐field practices. Farmers paying greater attention to non‐agricultural and social media sources were more likely to share and seek information. Attention to interpersonal sources was associated with greater adoption behaviors. This work highlights the importance of farmers' social networks, exposure to multiple information sources, and the need to identify new strategies for engagement and direct communication with hard‐to‐reach audiences. We conclude with a discussion of the implications of this work for conservation communication and land management practices to promote environmental health.